INOVASI PRODUK OLAHAN MAKANAN BERBAHAN BAWANG MERAH DALAM MENDUKUNG EKONOMI KREATIF DI KECAMATAN TOROH GROBOGAN - Astuti, Dwi Puji Astuti; Kardiyem, Kardiyem; Setiyani , Rediana; Aulia Prima Kharismaputra; Astuti, Abdul Khafidz (Jurnal Abdi Insani, 2024)
Shallots are a manipulation of local wisdom found in Grobogan Regency. One of the largest shallot planting centers in Grobogan Regency is Genangadal Village. The weak low bargaining position due to oversupply during the big harvest caused a drop in prices received by farmers. As an effort to provide solutions to these challenges, it is necessary to empower people to create a creative economy through processed product innovation. This activity aims to conduct training and assistance related to innovation in processing shallot-based products. In addition, it conducts training and assists in developing good product marketing strategies. The stages carried out in this service are Focus Group Discussion (FGD) with farmer groups, demonstrations and practices in making various preparations from shallots, tutorials and assistance on good marketing strategies, and monitoring and evaluation. Based on the training results, the potential of shallots, which was initially not optimally utilized by farmers, has now been optimized for use in products with high economic value. The shallots that have been processed are onion crackers and onion paste. In addition, farmers have also learned good product marketing strategies. This activity improves farmers' skills in producing various processed products with high economic value. In addition, the farmers also gained knowledge about the product's marketing strategy. This is undoubtedly a new market opportunity for farmers; when the price of shallots plummets, they don't have to worry anymore because they can take advantage of the harvest by making processed products with economic value.